Die Landnutzungskartierung in den Rheinlanden - Troll, Carl (ERDKUNDE, 1969)
Agrarian geography as a discipline goes back to the major books and atlases published by Th. H. Engelbrecht after 1898. The term agrarian geography (Agrargeographie) has been used since 1909, but first received methodological impetus from A. Ruhl (1929) and L. Waibel (1933). In connection with this, it was recognized that land-use should not only be recorded statistically by administrative units (Gemeinden, Kreise) but should be mapped in the field on large-scale maps. Only in this way is it possible to analyse the dependence of land-use on site conditions, not only those of agrarian ecology but also those of farm-enterprise and -sociology (e. g. ownership structure, distance from farmstead etc.). The first studies were carried out in the Mediterranean area and in Germany. Mapping soon switched from recording the fields of individual villages to mapping types of agrarian landscapes. Several working groups on agrarian geography were set up in the 1930's. The Geographical Institute in Bonn became a centre of land-use mapping. A complete land-use survey, such as that carried out under L. D. Stamp in Great Britain, was never attempted; instead, the analysis of individual agrarian landscapes based on large-scale mapping was carried out, together with the construction of corresponding historical land-use maps, particularly of the time before the agrarian and industrial revolution. From the multitude of individual projects, numerous examples are reviewed: 1. examples of historical change in agrarian landscapes (decline of viticulture, the spread of horticulture, de crease of shifting cultivation and other primitive rotations, the process of change to pasture and meadow (Vergrünlandung), new settlements of the 18th century); 2. examples of the mapping of intensive cultivation (viticulture, vegetable and orchard farming, tree nurseries, irrigation meadows, cultivation of basket willows and veneer poplars, greenhouse gardening etc.); 3. mapping of the fodder basis of animal husbandry, of pastures and meadows, forests and woodlands. After more than 20 years experience in land-use mapping, the first sheet of the general land-use map (at 1 : 100 000) of the Federal Republic of Germany (Sheet Cologne-Bonn) has been prepared in the Bonn Institute by W. Herzog and is included as Supplement III. Figure 1 shows the areas mapped to date.